Jab and Straight Punch of Extracurricular Boxing Athlete Panjaguru UPT SMA Negeri 7 Jeneponto - Latuheru, Ricardo Valentino; Ikadarny, Ikadarny (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research is a quantitative descriptive research. The subjects in the study were students of the extracurricular boxing Panjaguru Upt SMAN 7 Makassar. The research instrument used was the Jab And Straight Punch Speed Test. The number of samples used was 15 people. The processing of research data used descriptive statistics while the data analysis technique used was percentage. The results of the study of the ability to pass under the Jab And Straight Punches of Extracurricular Boxing Athletes Panjaguru Upt Sma Negeri 7 Jeneponto, for the "Very Good" category there were 0 students or 0%, the "Good" category there were 5 students or 33%, the "Enough" category there were 4 students or 27%, the "Less" category there were 4 students or 27%, the "Very Less" category there were 2 students or 13%. It can be concluded that the ability of volleyball underhand passing in SMAN 5 Soppeng students is in the "Good" category. While the results of the study of Smash ability of SMAN 5 Soppeng students for the "Very Good" category are 0 students or 0%, the "Good" category is 3 students or 20.0%, the "Enough" category is 9 students or 60.0%, the "Less" category is 2 students or 13.3%, the "Very Less" category is 1 student or 6.7%. It can be concluded that the Jab And Straight Punch of the Extracurricular Boxing Athletes of Panjaguru Upt SMA Negeri 7 Jeneponto is in the "Enough" category.